Tense and Text in Classical Arabic A Discourse-oriented Study of the Classical Arabic Tense System - Marmorstein, Michal (Studies in Semitic Languages and Linguistics, 2016)
In Tense and Text in Classical Arabic, Michal Marmorstein presents a discourse-oriented analysis of the indicative tense system in Classical Arabic. The study demonstrates the effect of the extended syntactic and textual context on the function of the verbal forms. Readership: Scholars of Classical Arabic syntax and discourse, Arabic grammatical tradition, comparative Semitic syntax, and anyone concerned with Arabic linguistics.